The Influence of Neuromarketing And User Interface on Consumer Satisfaction In E-Commerce Transactions (Study of USU Students Using the Shopee Platform in Medan) - Lie, Jeslyn; Simanjorang, Feronica; Siregar, Onan Marakali (Peneliti.net, 2025)
E-commerce is a buying and selling activity via the internet network where buyers and sellers do not meet directly, but communicate via the internet. This form of research uses quantitative research with an associative approach. The results in this study show that testing the first hypothesis obtained a significance value for the influence of neuromarketing (X1) on consumer satisfaction (Y) which was 0.000 < 0.05 and the tcount value was 4.344 > ttable 1.985. Testing the second hypothesis shows that the significance value of the influence of the user interface (X2) on consumer satisfaction (Y) is 0.000 < 0.05 and the t value is 10.325 > t table 1.985. The f test shows that the influence value of neuromarketing (X1) and user interface (X2) together or simultaneously on the consumer satisfaction variable is 0.000 < 0.05 and the calculated f value obtained is 172,403 > 3.090. The conclusion of this research is that neuromarketing (X1) and user interface (X2) partially have a positive and significant effect on consumer stasfaction (Y), and the variables neuromarketing (X1) and user interface (X2) simultaneously have a positive and significant effect on consumer satisfaction ( Y).